The perception of consumers from the North-East region of development of Romania of organic produce - Ioan Sebastian Brumă; Codrin Dinu Vasiliu; Lucian Tanasă; Sebastian Doboş (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
A significant amount of data and statistical information currently available indicates an ever-increasing appetite of European consumers for organic agri-food products. This particular phenomenon can be identified in Romania as well, albeit to a lower extent. In view of this, an analysis of Romanian consumers' perception of this particular category of produce, whether more succinct or extensive, is both necessary and useful in the shaping of a specific profile of this type of consumer. Consequently, in this study we discuss the interpretation of the data obtained by applying the 2016-2017 Ecological Agri-Food Products Questionnaire, which was developed within the Rural Development Research Platform Interdisciplinary Research Group and filled in by 1788 respondents, 723 of them residents of the North-East Development Region of Romania. The present research approach focuses on aspects of analysis based on demographic categories while aiming at observing the level of understanding of the term certified organic food-product, the main reason behind purchases, the criteria employed in recognizing organic agri-food products, the respondents' preference for certain purchase locations, customer familiarity with the logo specific to organic produce as well as the degree of confidence in organic food-products of the consumers in the North East Region of Development of Romania.
Keywords: Q57; P46; 330; organic food products; consumer profile